Towards Gender Equality in the Music Industry Education, Practice and Strategies for Change - Strong, Catherine; Raine, Sarah (Bloomsbury Academic, 2019)
Gender inequality is universally understood to be a continued problem in the music industry. This open access book presents research that uses an industry-based approach to examine why this gender imbalance has proven so hard to shift, and explores strategies that are being adopted to try and bring about meaningful change in terms of women and gender diverse people establishing ongoing careers in music. The book focuses on three key areas: music education; case studies that explore practices in the music industry; and activist spaces. Sitting at the intersection between musical production, the creative industries and gender politics, this volume brings together research that considers the gender politics of the music industry itself. It takes a global approach to these issues, and incorporates a range of genres and theoretical approaches. At a time when more attention than ever is being paid to gender and music, this volume presents cutting edge research that contributes to current debates and offers insights into possible solutions for the future. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Knowledge Unlatched.